2011
DOI: 10.1080/10810730.2010.535109
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Observational Coding Scheme for Analyzing Instrumental, Affective, and Relational Communication in Health Care Contexts

Abstract: Many observational coding schemes have been offered to measure communication in health care settings. These schemes fall short of capturing multiple functions of communication among providers, patients, and other participants. After a brief review of observational communication coding, the authors present a comprehensive scheme for coding communication that is (a) grounded in communication theory, (b) accounts for instrumental and relational communication, and (c) captures important contextual features with ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 62 publications
2
35
1
2
Order By: Relevance
“…Proper communication skills have often been neglected in medical education in the EU as well as in the USA (12). An important feature of communication processes is the fact that they can convey messages through multiple layers of verbal and nonverbal communication, and may indirectly facilitate the analysis of healthcare (13). Our study showed far lower rate in the subscale communication compared with Jagadeesan's study who reported the mean score in ophthalmological patients in this subscale 4.46 (14).…”
Section: The Quality Of Communication Betweencontrasting
confidence: 55%
“…Proper communication skills have often been neglected in medical education in the EU as well as in the USA (12). An important feature of communication processes is the fact that they can convey messages through multiple layers of verbal and nonverbal communication, and may indirectly facilitate the analysis of healthcare (13). Our study showed far lower rate in the subscale communication compared with Jagadeesan's study who reported the mean score in ophthalmological patients in this subscale 4.46 (14).…”
Section: The Quality Of Communication Betweencontrasting
confidence: 55%
“…Approaches include examination of linguistic structures that are primarily descriptive of verbal content during a communication interaction and process models to examine interactional behaviors. Communication provides two streams of meaning: one that regards the denotative content of a message and another that reflects the affective tone, and therefore the relational quality of the interactants (40). In the example study, interactions between the USPs and the physicians are audiotaped, transcribed and coded by trained research assistants.…”
Section: Resultsmentioning
confidence: 99%
“…A structured coding form was developed to measure patient-physician CRC screeningrelated discussion content and conversational techniques. Embedded in the coding form was an observational measurement system for identifying and analyzing various communication techniques, including the seven persuasive techniques of argument, refutation, altruism, esteem, guilt, foot in the door, and threat (see Table 1) [29]. In addition to this measurement system, qualitative content analyses resulted in the coding of one additional variable used in the current analyses: whether or not the patient was adherent to a previous physician recommendation for CRC screening [16].…”
Section: Data Sources and Measuresmentioning
confidence: 99%
“…The first consists of the communication (informational) content of the conversation and the second reflects the affective tone, which includes the social influence tactics employed in healthcare settings that impact decision-making [28]. The latter can include partnership-building, empathy, and persuasion, among other things [29]. Persuasion is a form of social influence whose use is widely acknowledged in healthcare decision-making.…”
mentioning
confidence: 99%